EFFECTIVENESS OF HEALTH SERVICES IN PUSKESMAS (Case Study in Bakun Village, Loloda Sub-district, Halmahera Barat District) State Administration Department Sam Ratulangi University Manado - Migar, Selfia; Lengkong, Florence Daicy; Palar, Novie (JURNAL ADMINISTRASI PUBLIK, 2017)
ABSTRACTThe purpose of this study is, to determine the effectiveness of health services in health centers Bakun Village District Loloda West Halmahera District. Benefits of research, As an information material for the district government, the District Government is also Bakun Village Government and the community The method used is Qualitative method with the type of descriptive approach And Location research in the village of Loloda Village District of West Halmahera. Based on the results of research The effectiveness of health services has not run well, then peneitian this to answer the question How the effectiveness of health services in Puskemas Bakun Village District Loloda West Halmahera District. In this study limits through some elements of effectiveness according to Gibson (1988) namely Production, efficiency, ability, adaptation / adjustment, development.Keywords: